2019
DOI: 10.12968/jowc.2019.28.6.416
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right rectangular expander and maximising the benefits from expanded tissue

Abstract: Objective: Tissue expanders are widely used in the reconstruction of tissue wounds. This study aims to demonstrate how to choose the correct size of rectangular expander in relation to wound size and the maximum advancement technique for wound coverage in order to achieve a successful outcome. Methods: The present study included patients who were operated on between January 2013 and January 2017. The expander height chosen was more than half the length of the wound and the expander width was chosen to be as wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The most important basis for any scar repair is tension-free closure 19 . Durgun and Aksam 20 stated in their retrospective study of 19 patients that height of the expanded tissue should be at least half of the wound length to allow for better wound coverage and repair. Hafezi et al 21 concluded, in a study of 48 cases with a total of 86 tissue expanders placed for treatment of head and neck burn scars, that overexpansion to more than 2 to 4 times the manufacturer's stated maximum volume provides better coverage of the defect with lower complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…The most important basis for any scar repair is tension-free closure 19 . Durgun and Aksam 20 stated in their retrospective study of 19 patients that height of the expanded tissue should be at least half of the wound length to allow for better wound coverage and repair. Hafezi et al 21 concluded, in a study of 48 cases with a total of 86 tissue expanders placed for treatment of head and neck burn scars, that overexpansion to more than 2 to 4 times the manufacturer's stated maximum volume provides better coverage of the defect with lower complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…8 Management of CMN can vary from observation to partial or completed surgical excision, with patient and caregiver preferences heavily influencing the approach taken. 9 The approach presented in this article enables surgeons to test different expander sizes and shapes, 10 different expander placement configurations, and different flap designs, allowing the surgeon to determine an optimal approach for each patient in advance of the operation. The approach also creates materials for patient and family education and feedback regarding the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A fresh opportunity was created by Radovan's invention [3]. Since then, TE has become an essential component used for the reconstruction of numerous congenital and acquired wounds in both children and adults [4]. There is an injection site where saline can be administered to inflate the expander, and it is made of a flexible and resilient silicone substance [4].…”
Section: Introductionmentioning
confidence: 99%